ACADEMIC PHRASE USED BY ENGLISH STUDENTS IN WRITING RESULTS SECTION IN THESIS - Esti Anjarwati; Washlurachim Safitri (Teaching English and Language Learning English Journal, 2024)
The objective of this research is to know the using of academic phrase in writing results section in students’ thesis. The design of this research using descriptive qualitative method. The data obtained using checklist table adapted by Swalles (1990). The result of this research found that the using of academic phrase in results section in students’ thesis written by English students academic year 2020. The results show that the results section of students thesis is unsufficient category. This research is expected to be an evaluation for students, it is suggested to other students to follow the academic phrase in each move by Swalles (1990) in writing results section. For further researcher, the results of this study can be refence for the future researcher who conducts research about writing results section. Keywords: academic phrase, results section, thesis